2021
DOI: 10.1093/jac/dkab252
|View full text |Cite
|
Sign up to set email alerts
|

Activity of meropenem/vaborbactam and comparators against Gram-negative isolates from Eastern and Western European patients hospitalized with pneumonia including ventilator-associated pneumonia (2014–19)

Abstract: Objectives Meropenem/vaborbactam has been approved in Europe for the treatment of hospital-acquired bacterial pneumonia, ventilator-associated pneumonia (VAP) and bacteraemia among other indications. Vaborbactam is an inhibitor of class A and C β-lactamases, including Klebsiella pneumoniae carbapenemase (KPC) enzymes, but not class B or D carbapenemases. We analysed the activity of meropenem/vaborbactam and comparators against 6846 Enterobacterales and 3567 Pseudomonas aeruginosa isolates fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…The primary carbapenemase in the present study was KPC (81.1%); the presence of MBLs (NDM and VIM) or OXA-48-like carbapenemases was uncommon (4.5% of isolates produced MBLs and 1.4% produced OXA-48-like carbapenemases). This is in contrast to findings for Europe, where MBL- and OXA-48-producing isolates are increasingly observed, particularly in Eastern European countries, where OXA-48 is becoming as common as KPC ( 6 , 23 25 ).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The primary carbapenemase in the present study was KPC (81.1%); the presence of MBLs (NDM and VIM) or OXA-48-like carbapenemases was uncommon (4.5% of isolates produced MBLs and 1.4% produced OXA-48-like carbapenemases). This is in contrast to findings for Europe, where MBL- and OXA-48-producing isolates are increasingly observed, particularly in Eastern European countries, where OXA-48 is becoming as common as KPC ( 6 , 23 25 ).…”
Section: Discussioncontrasting
confidence: 97%
“…It is possible that the high nonCP CRE rate reported by Tamma et al ( 26 ) represents a local clonal spread. The nonCP CRE rate for European CRE strains was 17.7% in the study by Sader et al ( 23 ), with Poland having a greater number than other European countries in additional recent studies ( 24 , 27 ).…”
Section: Discussionmentioning
confidence: 85%
“…Regarding HAP/VAP isolates, the drug was active against >90% of KPC-producing Enterobacterales and 70–80% of P. aeruginosa [ 74 , 75 ]. KPC-producing K. pneumoniae strains that develop resistance to CAZ/AVI often leads to MER/VARB cross-resistance through increased KPC expression, although some isolates remained susceptible to MER/VARB [ 76 , 77 ].…”
Section: Recently Approved Antimicrobial Agentsmentioning
confidence: 99%
“…In fact, in vitro studies showed very low MICs of the MEV combination for all tested Enterobacterales, which were known to be KPC-positive, OXA-48-negative and MBL-negative [ 67 ]. On the contrary, MEV showed little efficacy against MBL-producing CRE, DTR P. aeruginosa , S. maltophilia and A. baumannii in in vitro study [ 68 , 69 , 70 ]. The clinical efficacy of MER/VAB was evaluated in two phase 3 RCTs: TANGO I and TANGO II.…”
Section: Available Treatments For Carbapenem-resistant Gram-negative ...mentioning
confidence: 99%
“…MEV was specifically developed to target KPC-producing CRE [ 126 ]. A European survey among clinical isolates of inpatients with pneumonia showed that most isolated Enterobacterales were susceptible to MEV (98%; MIC50: 0.03 µg/mL; MIC90: 0.06 µg/mL) [ 68 ]. However, susceptibility to MER/VAB dropped to 63.0% (MIC50: 4 µg/mL; MIC90: >32 µg/mL) due to the presence of OXA-48- and MBL-producing strains of Enterobacterales.…”
Section: Available Treatments For Carbapenem-resistant Gram-negative ...mentioning
confidence: 99%